The individual poverty incidence of growth - Maria C. Lo Bue; Flaviana Palmisano (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The canonical approach to analysing the poverty impact of growth is based on the comparison of poverty before and after growth. Measurement tools that endorse this approach fail to capture the different experiences of poverty dynamics in the population: there can be groups of the population made poorer or non-poor made poor by growth. We propose an approach that allows measuring this individual poverty incidence of growth, and show how it relates to existing models. We apply our framework to evaluate the dynamics of the poverty impact of growth in Indonesia, by comparing the 1993-2000, 2000-07, and 2007-14 growth periods.
Keywords: D31; D63; I32; 330; growth; income mobility; Indonesia; poverty dynamics; pro-poorness